Morphological evidence for limited sperm production in the enigmatic Tasmanian cave spider Hickmania troglodytes (Austrochilidae, Araneae) - Michalik, Peter (2014)
The male reproductive systems of spiders are highly diverse in structure across all major spider taxa. Little is known about this organ system in basal araneomorph spiders, especially Austrochiloidea; such knowledge is necessary for a more complete understanding of the evolutionary morphology of the male reproductive system in spiders. In the present study, we describe the male reproductive system of an austrochilid spider, the enigmatic troglophilic Tasmanian cave spider Hickmania troglodytes, using light and electron microscopic techniques. The male reproductive system consists of tubular testes leading into convoluted deferent ducts, which are fused close to the genital opening to an unpaired ejaculatory duct. Spermatogenesis occurs only in the subadult testes, whereas adult testes showed neither spermatogenic stages nor any generative tissue in all investigated specimens. The testes of adult males are drastically reduced in size compared with those of subadult males, but the deferent ducts are filled with large numbers of mature spermatozoa. Thus, our data suggest that males of H. troglodytes are sperm-limited, but not necessarily spermdepleted as described for certain orb-weaving spiders. Due to the absence of generative tissue, limited sperm production is permanent (PSL) and probably has an influence on the reproductive strategies in this species. As nearly no data are available on the life history of H. troglodytes, and in particular information on the phenology of males is lacking, implications of the evolution of PSL in this species are unclear. Nonetheless, our data on other representatives of Austrochilidae (Austrochilus forsteri, Thaida chepu) and Gradungulidae (Progradungula otwayensis) suggest that PSL evolved within Austrochiliodea only in H. troglodytes and might be an adaptation to its troglophilic lifestyle.